The role of interleukin-converting enzyme in Fas-mediated apoptosis in HIV-1 infection. - Sloand, E M (1998)
Apoptosis of CD4+ lymphocytes is partially responsible for the depletion of these cells in HIV-infected individuals. CD4+ lymphocytes from HIV-1-infected patients express higher membrane levels of the Fas receptor, and are particularly susceptible to apoptosis after Fas triggering. IL-1beta- converting enzyme (ICE) is a key enzyme of the apoptotic machinery involved in Fas-mediated apoptosis of normal lymphocytes. The role of ICE in mediating the increased susceptibility of CD4+ lymphocytes from HIV-1-infected patients to apoptosis has not been examined. In this study, we found that ICE mRNA was present in T cells from both HIV-1-infected patients and controls. Active ICE proteins, p10 and p20, were demonstrated by immunoblot in lymphocytes from HIV-1-infected patients and in normal lymphocytes after treatment with Fas agonist, CH11 mAb. Cocultivation of lymphocytes from HIV-1-infected persons with Fas antagonist, antibody ZB4, resulted in decreased expression of ICE protein in lymphocytes from HIV-infected patients, and decreased apoptosis. Similar effects were obtained when cells were treated with synthetic ICE inhibitors, which blocked apoptosis in response to Fas triggering. When CD4+ and CD8+ cells were sorted by flow cytometry and analyzed by reverse transcriptase PCR, ICE mRNA was present in both CD8+ and CD4+ cells. However, flow cytometric analysis of lymphocytes with intracellular staining for ICE demonstrated ICE protein in the CD4+ but not the CD8+ cell fraction derived from blood of HIV-1-infected patients. These data suggest that activation of ICE occurs in vivo in CD4+ lymphocytes from HIV-1-infected individuals, and may account for the increased susceptibility of CD4+ cells to apoptosis.